Penerapan Motion UI untuk Meningkatkan Pengalaman Pengguna dan Penyampaian Informasi pada Website Kampus - Ramadhanti, Jihan Arifia; Isyriyah, Laila; Maulidi, Rakhmad (LPPM STIKI MALANG, 2025)
This research aims to develop a campus introduction website interface for STIKI Malang by implementing Motion UI to enhance information delivery effectiveness and user experience. Currently, the STIKI website uses a multi-page structure that requires visitors to open sub-menus separately to access information, resulting in significant resource consumption and long loading times. By transforming the website structure into a single-page application (SPA) and integrating dynamic animation elements through Motion UI, it is expected to increase engagement and conversion rates. Qualitative analysis results show significant improvements in user engagement and information comprehension, with page loading times drastically reduced to an average of 2.6 seconds. Evaluation using the User Experience Questionnaire (UEQ) also demonstrates significant improvements in attractiveness, clarity, efficiency, and stimulation aspects. This research concludes that implementing Motion UI on STIKI's single-page website successfully enhances user experience, access speed, and information delivery effectiveness. The results of this research can serve as a reference for developing interface design strategies for other educational institution websites